Differentiation-Driven Nucleolar Association of the Mouse Imprinted Kcnq1 Locus - Fedoriw, Andrew M. (Genetics Society of America, 2012)
The organization of the genome within the mammalian nucleus is nonrandom, with physiologic processes often concentrated in specific three-dimensional domains. This organization may be functionally related to gene regulation and, as such, may play a role in normal development and human disease processes. However, the mechanisms that participate in nuclear organization are poorly understood. Here, we present data characterizing localization of the imprinted Kcnq1 alleles. We show that nucleolar association of the paternal allele (1) is stimulated during the differentiation of trophoblast stem cells, (ii) is dependent upon the Kcnq1ot1 noncoding RNA, (3) does not require polycomb repressive complex 2, and (4) is not sufficient to preclude transcription of imprinted genes. Although nucleolar positioning has been proposed as a mechanism to related to gene silencing, we find that silencing and perinucleolar localization through the Kcnq1ot1 noncoding RNA are separable events.